"Revenge of the East"?: The AfD's Appeal in Eastern Germany and Mainstream Parties' Responses. Issue 2 (1st June 2020) - Yoder, Jennifer A.
Abstract: This article examines the ways the Alternative for Germany (AfD) has claimed to supply eastern voters with important elements of political representation that they demand. Rather than seeking "revenge, " which would suggest voting purely out of protest against a government or policy, the evidence examined in this article suggests that some voters in the East support the AfD to express something else. The reactions of some of the other political parties in the wake of recent elections suggest that they have begun to pay more attention to their roles in the electorate and to the various dimensions of political representation.